REALIZING SUSTAINABLE AGRICULTURE WITH EMPOWERMENT AND APPLICATION OF BIOSAKA INNOVATION TECHNOLOGY IN SEUMANTOK VILLAGE, WEST ACEH - Dewi Andriani; Lias Harapan; Fantashir Awwal Fuqara; Jekki Irawan; Putri Mustika Sari; Abdul Muzammil; Anisah Nasution (RADJA PUBLIKA, 2024)
The problem of unbalanced use of inorganic fertilizers and in the long term it can cause damage to the physical, chemical and biological properties of the soil as well as changes in the balance of soil nutrients, so that it produces unproductive marginal land for sustainable crop cultivation. Biosaka can be an effective and efficient innovation to reduce dependence on the use of inorganic fertilizers and minimize farming production costs. This community service was carried out in Seumantok Village, West Aceh. Methods for implementing community service include socialization, technical guidance in making biosaka and evaluation with questionnaires. The results obtained by the community are able to understand the meaning of biosaka and its benefits, how to make biosaka, and how to apply biosaka to cultivated plants. This biosaka eliminator is expected to be able to have a good effect on agricultural land, able to reduce the use of inorganic materials and maximize crop production potential in Seumantok Village, West Aceh.